Levels of prostaglandin E2 and Cysteinyl‐leukotrienes in sputum supernatant of patients with asthma: the effect of smoking. Issue 6 (28th May 2013) - Kontogianni, K.; Bakakos, P.; Kostikas, K.; Hillas, G.; Papaporfyriou, A.; Papiris, S.; Koulouris, N. G.; Loukides, S.
Summary: Background: Smoking is associated with worse asthma outcomes and may modify airway inflammation. Such modification may be mediated through an effect on prostaglandin E2 (PGE2 ) and cysteinyl leukotrienes (Cyst‐LTs). Objective: We aimed to determine the levels of both PGE2 and Cyst‐LTs in sputum supernatants of patients with asthma and to investigate the effect of smoking habit as well as their associations with inflammatory cells, bronchial hyperresponsiveness (BHR) and lung function. Methods: Ninety‐eight patients to asthma (47 smokers) and 40 healthy subjects (20 smokers) were studied. All subjects underwent sputum induction for cell count identification, PGE2 and Cyst‐LTs levels measurement in supernatants, pulmonary function tests and BHR to methacholine. Results: Patients with asthma had significantly higher levels of both Cyst‐LTs and PGE2 in sputum supernatants compared to healthy subjects [median (interquartile ranges) 432 (287, 575) vs. 91.5 (73.5, 111) pg/mL and 654 (456, 789) vs. 117.5 (92, 157) pg/mL, respectively, P < 0.001 for both comparisons]. Smoking asthmatics had significantly higher Cyst‐LTs and PGE2 levels compared to non‐smoking asthmatics. Cyst‐LTs levels in sputum supernatant of smoking asthmatics presented a significant positive association with sputum eosinophils, while PGE2 levels were positively associated with sputum neutrophils. Conclusions: The increased concentrations of PGE2 and Cyst‐LTs in sputum supernatants of smoking asthma are consistent with an up‐regulation of these two mediators in this specific phenotype of asthma. Furthermore, Cyst‐LTs are associated with eosinophilic inflammation, while PGE2 is associated with the presence of neutrophilic inflammation in smoking asthma.